Mineralogy and geochemistry of deeply-buried marine sediments of the Vaca Muerta-Quintuco system in the Neuquén Basin (Chacay Melehue section), Argentina: Paleoclimatic and paleoenvironmental implications for the global Tithonian-Valanginian reconstructions. (April 2021) - Capelli, Ignacio A.; Scasso, Roberto A.; Spangenberg, Jorge E.; Kietzmann, Diego A.; Cravero, Fernanda; Duperron, María; Adatte, Thierry
Abstract: The Vaca Muerta-Quintuco (VM-Q) system of Tithonian-early Valanginian age was studied in the Chacay Melehue section of the Neuquén Basin (western Argentina) by means of sedimentological, mineralogical and geochemical analyses in order to determine the main driving factors that triggered the paleoenvironmental change from a carbonate ramp (Vaca Muerta Formation, VMFm) to a mixed siliciclastic/carbonatic marine environment (Quintuco Formation, QFm). The VMFm was divided into two stratigraphic intervals: Lower VMFm (LVMFm) and Upper VMFm (UVMFm), whereas the QFm is subdivided into the Puesto Barros Member (PBMb) and the Cerro La Visera Member (CVMb), which can be correlated to other sections in the basin (e.g., Puerta Curaco). Isolated, turbiditic sandstone beds, correlated to the Huncal Member, are included in the QFm. The LVMFm (Tithonian) and the UVMFm (Berriasian) are constituted by dark, well-laminated marls, mudstones, calcite concretions and tuffs. The PBMb (earlier early Valanginian) is constituted by marls and sandstones, whereas the CVMb (later early Valanginian) is constituted by marls, mudstones, siltstones, sandstones and coquinas. The LVMFm (Total organic carbon, TOC 1–4 wt%) is characterized by the enrichment of redox sensitive trace elements (RSTE), where the enrichment of Ni and Cu suggest high productivity in the water column, and the enrichment of Mo, U, V points to sea bottom anoxia, with periods of increased oxygenation as deduced from higher P concentrations in marls and mudstones. The clay mineral association is constituted by mixed-layer illite/smectite formed by the transformation of smectitic layers. The predominance of smectite in coeval sucessions, less overprinted by burial diagenesis, suggests a temperate and semi-arid climate in the adjacent continent. The UVMFm (TOC >1 wt%) is characterized by a gradual decrease of the RSTE pointing to a decrease in productivity and a slight increase in the oxygenation of the sea bottom. In addition, a change towards more humid conditions in the continent is inferred by both the increase in the Chemical Index of Alteration and the Al2 O3 /TiO2 ratio. The PBMb (TOC 1 wt%) has even lower content of RSTE indicating diminished sea water productivity and a gradual rise of the oxygenation of the sea bottom. In this interval, increased illite contents suggest periods of enhanced physical weathering, probably related to the tectonic uplift of the Huincul Ridge. The RSTE in the CVMb (TOC <1 wt%) documents a fully oxygenated sea bottom, where the productivity of the water column was negligible. The presence of kaolinite and the increment of the detrital sedimentation in the CVMb indicate a change towards more humid conditions in the hinterlands. The enhanced runoff caused by this paleoclimatic change towards more humid conditions that started in the early Berriasian and increased during the later early Valanginian triggered the change from carbonate ramp to mixed siliciclastic/carbonatic to siliciclastic marine paleoenvironments. The organic carbon isotope composition (δ 13 Corg vs. VPDB) of the VMFm ranges between −30.0 and −23.4‰, whereas in the QFm values range between −29.0 and −23.9‰. Two positive carbon isotope excursions (PCIE) are recorded in the system: PCIE-A in the lower part of the VMFm (early Tithonian) with δ 13 Corg values −25‰, and PCIE-B in the upper part of the QFm (later early Valanginian) with δ 13 Corg values −24.5‰. The shift in δ 13 Corg at PCIE-B is up to +4.2‰ and marks the onset of the Weissert Event. This is the first time that the onset of this event is recorded in the Neuquén Basin, within the Lissonia riveroi ammonite zone. The results of our study confirm that clay mineralogy, trace elements and stable isotopes are valuable proxies of past ocean-climate variability even in sediment deposits that underwent near-surface and deep burial diagenesis. Highlights: The Vaca Muerta-Quintuco system underwent deep burial diagenesis. Paleoclimatic changes towards more humid conditions are recorded in the Berriasian. The climatic changes played a key role in the environmental evolution. Positive carbon isotope excursions are recorded in the Tithonian and Valanginian.